PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER PESERTA DIDIK - Halimatussa’diah; Syukron; Dedi Irawan (UNISAN JURNAL, 2025)
Education is a lifelong process, from birth to death. Education must be organized in an open system that allows for flexibility of choice and timing of program completion across educational units and pathways. The purpose of this study was to analyze the personality competencies of Islamic Religious Education teachers in fostering the morals of students at SD Negeri 005 Tanjung Palas Tengah Kabupaten Bulungan , South Sumatra Province. This research is descriptive qualitative. Data collection is done by means of interviews, observation, and documentation. Data were analyzed by means of data reduction, data presentation and drawing conclusions. The results of the research on Personality Competence of Islamic Religious Education Teachers in Fostering the Morals of Students at SD Negeri 005 Tanjung Palas Tengah Kabupaten Bulungan Junior High School can already be carried out properly